THE USE OF VIRTUAL REALITY (VR) / AUGMENTED REALITY (AR) AS LEARNING MEDIA IN SCIENCE AND SOCIAL STUDIES SUBJECTS IN ELEMENTARY SCHOOL - Devi Rahmiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to identify the use of Virtual Reality (VR) and Augmented Reality (AR) as educational media in the Science and Social Studies (IPAS) subjects at the elementary school level. VR and AR are considered technologies that can enhance students' learning experiences by providing interactive visualizations and immersive learning environments. These media allow students to better understand abstract concepts in IPAS through in-depth visual simulations and explorations. The study utilizes a literature review method, using the keyword "VR/AR media in elementary education." The focus is on the use of VR/AR as learning media for IPAS subjects in elementary schools. Literature sources include articles collected through search engines such as Publish or Perish (POP), VOSviewer, and SINTA, focusing on articles published within the last five years. The research results show that the use of VR and AR in the learning process has a positive impact and can enhance students' learning outcomes and higher-order thinking skills (HOTS) in real-life applications. Therefore, it is recommended that VR and AR be more broadly applied to support more effective and innovative learning in elementary schools.